Geographical chemical variability and processing oxidation of volatile compounds of Casearia sylvestris leaves - Carvalho, Flavio Alexandre [UNESP]; Oda, Fernando Bombarda [UNESP]; Crotti, Antonio Eduardo Miller; Crevelin, Eduardo Jose; Dos Santos, Andre Gonzaga [UNESP] (My University, 2021)
The Casearia sylvestris Sw. dried leaf essential oil (EO) contains sesquiterpenes as the main components. However, the volatile components in the in natura leaves remain unknown. This study compares the volatile chemicals in the in natura leaves and dried leaf EO of two C. sylvestris populations from Atlantic Forest and Cerrado. The volatile compounds were directly analysed by thermal desorption (TD) coupled to gas chromatography mass spectrometry (GC-MS); the dried leaf EO composition was determined by GC-MS. All the identified compounds were sesquiterpenes, and the major components were (E)-caryophyllene, bicyclogermacrene, β-elemene, spathulenol, and caryophyllene oxide. In both populations, the sesquiterpene hydrocarbon content and the oxygenated sesquiterpene content respectively decreased and increased on going from the in natura leaves to the dried leaf essential oil, indicating that drying and/or hydrodistillation modified the volatile chemical composition by generating oxidation artifacts. Results suggested that (E)-caryophyllene and bicyclogermacrene may be oxidized during the process to yield caryophyllene oxide and spathulenol, respectively. The two C. sylvestris populations also differed in terms of volatile chemical composition.
Keywords: Artifacts; Essential oil; Hydrodistillation; Sesquiterpenes; Thermal desorption